Access to Maternal Health Services during COVID-19 - Pant, Smriti; Koirala, Saugat; Subedi, Madhusudan (Europasian Journal of Medical Sciences, 2020)
Most causes of maternal morbidity and mortality can be prevented by giving prompt, suitable treatment to the women by qualified health practitioners. Maternal health services (MHS), which include antenatal care, delivery care, and postnatal care, can play a crucial role in preventing maternal health problems. The recent coronavirus disease (COVID-19) pandemic has had a disastrous effect on the health care delivery system of people of all ages, on a global scale but pregnant women face particular challenges. The aim of this review is to assess the effect of COVID-19 on access to MHS. For writing this narrative review, national and international reports on maternal health services during COVID-19, along with journal articles on the related topic were reviewed. Due to this pandemic, women worldwide are facing more barriers to accessing maternal health care, including restrictions, transport challenges, and anxiety over possibly being exposed to coronavirus. Many women preferred not to seek healthcare due to the fear of themselves being infected with the virus or transmitting it to their unborn babies. Additionally, movement restriction has made it difficult for many pregnant women to reach health care facilities. Even those who managed to reach health facilities have reported not receiving timely care. As a result, a considerable rise in maternal mortality globally has been estimated over the next six months. Despite the circumstances, efforts have been made to boost maternal health in both developed and developing countries. This pandemic has highlighted the importance of health preparedness with special attention given to vulnerable people like pregnant women and newborns while planning for such events.